Productivity and SDS-sedimentation of the promising winter bread wheat varieties depending on forecrops - M. M. Kopus; N. S. Kravchenko; Yu. N. Alty-Sadykh; M. M. Ivanisov; A. P. Samofalov (Зерновое хозяйство России, 2022)
The main purpose of breeding and commercial production is the quantity of grain and its quality. Occupying 74 % in the structure of grain crops, and 80 % in terms of gross yields, wheat grain is the most important source of income for grain producers in the Rostov region. The purpose of the current study was to reveal the effect of forecrops on productivity and SDS-sedimentation of the promising winter bread wheat varieties. In the trial there were studied 12 winter bread wheat varieties developed by the FSBSI “ARC “Donskoy” and sent to the State Variety Testing in recent years. There were estimated productivity and the amount of SDS-sedimentation. On average, over the three years of study (2019–2021), for all the studied forecrops, in terms of productivity there have been identified such winter wheat varieties of the intensive type as ‘Razdolie’ (7.14 t/ha), ‘Razgulay’ (7.67 t/ha) and ‘Vasilich’ (7.51 t/ha), which makes it possible to recommend these genotypes for sowing according to high and medium levels of Agricultural background. Among winter wheat varieties of semi-intensive type there has been identified only one variety ‘Donets’ (7.31 t/ha), which allows us to characterize it as a universal variety and recommend it for sowing in production according to high, medium and low levels of Agricultural background. According to the value of SDS-sedimentation for all the studied forecrops, there have been identified such varieties of intensive type as ‘Razdolie’ (62 ml), ‘Azov Sea’ (61 ml), ‘Razgulay’ (63 ml) and ‘Vasilich’ (63 ml). The varieties of semi-intensive type did not significantly exceed the value of SDS-sedimentation of the standard variety or were at its level, however, the values were high. Such SDS-sedimentation values have indicated that the presented genotypes are able to form high grain quality for all the studied forecrops and regardless of the productivity value.